2019
DOI: 10.2147/cmar.s196372
|View full text |Cite
|
Sign up to set email alerts
|

<p>Apatinib enhances chemosensitivity of gastric cancer to paclitaxel and 5-fluorouracil</p>

Abstract: Background and aim: Paclitaxel (PTX) plus 5-fluorouracil (5-Fu) has become the standard chemotherapy for advanced gastric cancer (GC). Apatinib, a small-molecule tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2, improves outcomes in GC patients as a third-line treatment. However, its impact on the chemosensitivity of GC remains to be determined. Hence, we aimed to assess the efficacy and safety of apatinib combined with chemotherapy in vivo and in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…Previous studies about bevacizumab demonstrated that anti-angiogenic agents should be better discontinued at least 5–8 weeks prior to surgery and not be restarted until 28 days after the surgery in the setting of neoadjuvant and conversion therapy of metastatic colorectal cancer ( Gruenberger et al, 2008 ; Xu et al, 2019a ). Our data confirmed that, the duration of withdrawal apatinib for 4 weeks, the interval between radical gastrectomy and the last dose of apatinib, did not increase the rate of complications in metastatic GC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies about bevacizumab demonstrated that anti-angiogenic agents should be better discontinued at least 5–8 weeks prior to surgery and not be restarted until 28 days after the surgery in the setting of neoadjuvant and conversion therapy of metastatic colorectal cancer ( Gruenberger et al, 2008 ; Xu et al, 2019a ). Our data confirmed that, the duration of withdrawal apatinib for 4 weeks, the interval between radical gastrectomy and the last dose of apatinib, did not increase the rate of complications in metastatic GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the previous article ( Xu et al, 2019a ), apatinib was administered at a dose of 500 mg once a day continuously. PTX at a dose of 130 mg/m 2 was given on day 1 as a 2 h intravenous infusion with standard premedication.…”
Section: Methodsmentioning
confidence: 99%
“…Zygote period cleaving eggs were transferred to six-well plastic cell culture plates filled with embryo medium E3. The eggs (10-12 per well) were exposed to RSC (50 mM), 5-FU (50 mM), and MM-129 (10 mM) for 3 h 24,25 . The final volume of the medium in each well was 2 mL.…”
Section: Zebrafish Drug-screening Assaymentioning
confidence: 99%
“…These findings were confirmed in a phase II study, which showed that the monotherapy achieved an OR of 7.7%, with median PFS and OS at 4.63 and 6.57 months, respectively [ 31 ]. Moreover, in vivo and in vitro studies have demonstrated that apatinib significantly increased the sensitivity to paclitaxel, cisplatin, and 5-Fu, suggesting that it is feasible to combine apatinib with other chemotherapeutic agents to yield a synergistic effect [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%